Overview of Baby Blues Syndrome Incidence in Postpartum Mothers Based on Sociodemography during the COVID-19 Pandemic - Endang Khoirunnisa; Kurniasari Pratiwi; Eny Retna Ambarwati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine overview of baby blues syndrome incidence in postpartum mothers based on sociodemography during the coronavirus disease 2019 (COVID-19) pandemic. The type of research conducted is quantitative research with analytical descriptive research method with a cross sectional study approach. The population of this study were all mothers who gave birth to live babies in all provinces in Indonesia in 2019 totaling 4,778,621. The sampling method is using quota sampling. The measuring instrument for post partum blues used in this study is the Edinburgh Postnatal Depression Scale (EPDS). The analysis of this study used univariate and bivariate analysis. Based on the results of the study, there is no relationship between parity and baby blues syndrome. There is a relationship between caregiver assistants and baby blues syndrome. There is a relationship between the place of residence after childbirth and baby blues syndrome. There is no relationship between ethnicity and baby blues syndrome.